Expression of TNF-superfamily members BAFF and APRIL in breast cancer: Immunohistochemical study in 52 invasive ductal breast carcinomas - Stathopoulos Efstathios N; Tsiftsis Dimitrios D; Sanidas Elias; Darivianaki Katerina; Kafousi Maria; Kampa Marilena; Pelekanou Vassiliki; Tsapis Andreas; Castanas Elias (BMC Cancer, 2008)
Abstract Background Recent studies suggest an association between chronic inflammation, modulating the tissue microenvironment, and tumor biology. Tumor environment consists of tumor, stromal and endothelial cells and infiltrating macrophages, T lymphocytes, and dendritic cells, producing an array of cytokines, chemokines and growth factors, accounting for a complex cell interaction and regulation of differentiation, activation, function and survival of tumor and surrounding cells, responsible for tumor progression and spreading or induction of antitumor immune responses and rejection. Tumor Necrosis Factor (TNF) family members (19 ligands and 29 receptors) represent a pleiotropic family of agents, related to a plethora of cellular events from proliferation and differentiation to apoptosis and tumor reduction. Among these members, BAFF and APRIL (CD257 and CD256 respectively) gained an increased interest, in view of their role in cell protection, differentiation and growth, in a number of lymphocyte, epithelial and mesenchymal structures. Methods We have assayed by immunohistochemistry 52 human breast cancer biopsies for the expression of BAFF and APRIL and correlated our findings with clinicopathological data and the evolution of the disease. Results BAFF was ubiquitely expressed in breast carcinoma cells, DCIS, normal-appearing glands and ducts and peritumoral adipocytes. In contrast, APRIL immunoreactive expression was higher in non-malignant as compared to malignant breast structures. APRIL but not BAFF immunoreactivity was higher in N+ tumors, and was inversely related with the grade of the tumors. Neither parameter was related to DFS or the OS of patients. Conclusion Our data show, for the first time, an autocrine secretion of BAFF and APRIL from breast cancer cells, offering new perspectives for their role in neoplastic and normal breast cell biology and offering new perspectives for possible selective intervention in breast cancer.